The dissociation pathways and isotope effects in intense field dissociation of H2+ and HD+. (30th August 2019) - Yao, Hongbin; Sun, Zhaopeng; Jiang, Xiangzhan; Cao, Changhong
Abstract: The dissociation pathways and isotope effects in intense field dissociation of the homonuclear and its inhomonuclear isotope HD + has been investigated by using an accurate 3D non-Born–Oppenheimer approach. The models of the photon-dressed states are presented to analyze the possible dissociation pathways of the and HD + systems. Comparing the kinetic energy resolved spectra of and HD +, the dissociation pathways are clearly distinguished for the and HD + molecules, and that are highly dependent on the laser intensity. Most importantly, the direct two-photon dissociation of HD + occurs at the intensity of 2.0 × 10 14 W cm −2, which is forbidden in the . However, it converts into the net one-photon dissociation as the laser intensity decreases to 4.0 × 10 13 W cm −2 . This conclusion could provide the scientific prediction and theoretical guidance to the experiment in the future.